Oscillator Finite-Difference Time-Domain (O-FDTD) electric field propagation model: integrated photonics and networks - Adão Ricardo M. R. (EDP Sciences, 2021)
The recently developed Lorentz Oscillator Model-inspired Oscillator Finite-Difference Time-Domain (O-FDTD) is one of the simplest FDTD models ever proposed, using a single field equation for electric field propagation. We demonstrate its versatility on various scales and benchmark its simulation performance against theory, conventional FDTD simulations, and experimental observations. The model’s broad applicability is demonstrated for (but not limited to) three contrasting realms: integrated photonics components on the nano- and micrometer scale, city-wide propagating radiofrequency signals reaching into the hundreds of meters scale, and for the first time, in support of 3D optical waveguide design that may play a key role in neuromorphic photonic computational devices.